Lewi Pethrus' ecclesiological thought, 1911-1974 : a transdenominational pentecostal ecclesiology - Davidsson, Tommy H. (Global Pentecostal and Charismatic Studies, 2015)
In Lewi Pethrus' Ecclesiological Thought 1911-1974: A Transdenominational Pentecostal Ecclesiology , Tommy Davidsson presents a chronological survey of the ecclesiology of the Swedish Pentecostal pioneer, Lewi Pethrus (1884-1974). The presentation is the first study of its kind and it demonstrates by means of a historical analysis the underlying factors that contributed to the formation of ecclesiological beliefs among Pentecostals. The insights from the historical analysis are then applied to a global setting. By employing Roger Haight's Transdenominational Ecclesiology, Davidsson proposes a methodology that serves as a helpful tool when assessing the unifying values that characterise highly diverse Pentecostal communities worldwide.